joool

posted by .

3y^2-6x^2-3xy=0

  • joool -

    3(y^2 - xy - 2x^2) = 0
    3(y-2x)(y+x) = 0

    y=2x or y = -x

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. bobpursly,

    Is this correct now after i revised it Multiply. 3xy^2(5xy-4x+6y) 3xy^2(5xy)=15x^2y^3 3xy^2(-4x)=-12x^2y^2 3xy^2(6y)=18xy^3 so i get from this 15x^2y^3-12x^2y^2+18xy^3 correct awsome i just thought that the 15x^2y^3-12x^2y^2 should …
  2. Math

    I have no clue how to do this as no values were given and im confused. can someone explain plz?
  3. differential equations

    the directions are to determine whether or not the equation is exact if so then solve it. the question is (x-y^3+ysinx)dx = (3xy^2+2ycosx)dy i solve and i got that it is exact because My is -3y^2+2ysinx and Nx is -3y^2+2ysinx since …
  4. Algebra-Please check my answers

    Posted by Jessie on Monday, October 18, 2010 at 3:48pm. I think I figured it out-please check I'm really stuck on these problems- Simplify 6xy(3xy)^-2?
  5. Algebra-Please check my answers

    Posted by Jessie on Monday, October 18, 2010 at 3:48pm. I think I figured it out-please check I'm really stuck on these problems- Simplify 6xy(3xy)^-2?
  6. Derive

    Find the derivative of sin(2x + 3y)= 3xy + 5y-2. I have this so far 1) cos(2x+3y) * d/dx (2x+3y)= 3xy' + 3y + 5y' 2) cos (2x+3y) * [2 + 3y']= 3xy' + 3y + 5y' 3) 3y' cos (2x+3y) + 2cos(2x+3y)= 3xy' + 3y + 5y' 4) 3xy' + 5y' - (3y(cos(3x+3y)= …
  7. Math help polynomial

    multiply the following polynomial -3x(y^2+2y^2) answer choices 3xy^2-6xy^2' -3xy^2-gxy^2 -3xy^2+5y^2 -9xy^2 The last one was the answer. Can you tell me how the answer was solved?
  8. Math!

    1) What is the value of 19 + 5a^4 + 3b^2 when a = 2 and b = -4?
  9. Simultaneous equation

    X+y+z=1......(1) x^2+y^2+z^2=35........(2) x^3+y^3+z^3=97.........(3) solution but from 3 (x^3+y^3)=(x+y)^3-3xy(x+y)......(4) puting 4 into 3 bck (x+y)^3-3xy(x+y)+z^3=97.......(5) now from 1 x+y=1-z......(6) putin 6 into 7 we have …
  10. polynomials

    I have to simplify (-x^5y^4)^4(3x^2y)^2(1/3xy) I did (x^20y^16)(9x^4y^2)(1/3xy) (9x^24y^18)(1/3xy) 3x^25y^19 Is this correct?

More Similar Questions